Portafolio de instrumentos hacia la acción climática y la construcción de paz. - Yomayuza, Karoll Valentina; Vanegas, Martha; Borda, Carlos Andrés; Casallas Martinez, Ivon; Diaz, Lizette Maritza; Hurtado, Jhon Jairo; Calderon, Victor Hugo; Velez, Andres Felipe; Castro Nunez, Augusto (2024)
This document outlines the integration of sustainable practices in the cocoa sector, aimed at promoting climate action and peacebuilding in regions affected by deforestation and conflict. It highlights the role of business models that incorporate small-scale producers, with a focus on enhancing business models and fostering market connections. The approach seeks to build resilience against climate change while contributing to the achievement of the Sustainable Development Goals (SDGs)